"Life in the camps makes you sick." Results of a photovoice project with refugees in Munich, Germany. (20th October 2021) - Namutebi, L; Nakyazze, OC; Bamuwayira, A; Huber, A; Krasniqi, S
Abstract: Background: Refugees newly arriving in Germany are housed in large accommodation centers. Living in such camps make it difficult to stay healthy due to the psychological stresses associated with the loss of privacy, the hygienic conditions and the bad nutrition. While these conditions are known, few studies exist that capture the lived experiences of refugees in such shelters. Methods: The project 'Vulnerability and empowerment: Participatory approaches to health promotion with refugees' (EMPOW), funded by the German Research Foundation (2019-2022) applies a participatory design involving three study sites. In Munich, the Photovoice method was used to identify health challenges in the camps. Examples are shown and discussed. Results: Being forced to live in camps constitutes a specific hazard to the health of refugees. Often, they are not allowed to cook or to bring their own food. Canteens, bedrooms and sanitary facilities are shared with many people, which poses a major hygiene problems (especially during the Corona pandemic). Particularly for pregnant women this situation is harmful to their health. The COVID-19-pandemic worsens these problems significantly e.g. via quarantine measures that are imposed on shelters and its inhabitants for long periods. Conclusions: The photovoice stories document the serious deficits of the shelter system from a community perspective showing how these are detrimental to the inhabitants' health. Suggestions are made for improving the situation so that persons seeking asylum in Germany have better chances to stay healthy. The perspective of refugees themselves on these challenges must be taken seriously in order to improve their health. Main messages: Photovoice provides a tool for refugees to express and interpret their lived experiences. The shelter system in Germany is detrimental to the health of refugees.